(3cJGH GdJHjjf dCSeGA GdeOdSjfs - (3EHQGgje Hf eMeO Hf Ndjd GdnqWnQGoHodSj Ke GdMdHj, CHh GdhaGA, HQgGf GdOjf, pSrHW GHf GdnYnLej , J (B841 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPG JYdjb ai CSeGA GdeOdSjf cfJ bO LeYJg bOjekG ai JYdjb di Ydi SjQI CHj GdadM GdjYeQi s
(3BNQgG (B:s
(3bGd GdMGce dG CYQa ai GdeJCNQjf ef jPcQ Hg EdG CHG HcQ eMeO Hf eMeO Hf SdjeGf GdHGYfOdi hGddg CYde GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B343s
Keywords: (3GdMOjK h GdeUWdMs